In silico target network analysis of de novo-discovered, tick saliva-specific microRNAs reveals important combinatorial effects in their interference with vertebrate host physiology - Hackenberg, Michael; Langenberger, David; Schwarz, Alexandra; Erhart, Jan; Kotsyfakis, Michail (RNA (New York, N.Y.), 2017)
The hard tick Ixodes ricinus is an important disease vector whose salivary secretions mediate blood-feeding success on vertebrate hosts, including humans. Here we describe the expression profiles and downstream analysis of de novo-discovered microRNAs (miRNAs) expressed in I. ricinus salivary glands and saliva. Eleven tick-derived libraries were sequenced to produce 67,375,557 Illumina reads. De novo prediction yielded 67 bona fide miRNAs out of which 35 are currently not present in miRBase. We report for the first time the presence of microRNAs in tick saliva, obtaining furthermore molecular indicators that those might be of exosomal origin. Ten out of these microRNAs are at least 100 times more represented in saliva. For the four most expressed microRNAs from this subset, we analyzed their combinatorial effects upon their host transcriptome using a novel in silico target network approach. We show that only the inclusion of combinatorial effects reveals the functions in important pathways related to inflammation and pain sensing. A control set of highly abundant microRNAs in both saliva and salivary glands indicates no significant pathways and a far lower number of shared target genes. Therefore, the analysis of miRNAs from pure tick saliva strongly supports the hypothesis that tick saliva miRNAs can modulate vertebrate host homeostasis and represents the first direct evidence of tick miRNA-mediated regulation of vertebrate host gene expression at the tick-host interface. As such, the herein described miRNAs may support future drug discovery and development projects that will also experimentally question their predicted molecular targets in the vertebrate host.
Keywords: Ixodes; tick–vertebrate host interaction; interactomes/systems biology; MicroRNAs; genové regulační sítě; Computer Simulation; obratlovci; microRNA; Salivary Glands; Host-Parasite Interactions; klíště; Gene Regulatory Networks; deep-sequencing; Vertebrates; zvířata; Saliva; počítačová simulace; slinné žlázy; transkriptom; infestace klíšťaty; sliny; vysoce účinné nukleotidové sekvenování; disease biology; Transcriptome; High-Throughput Nucleotide Sequencing; gene target prediction; mikro RNA; Animals; Tick Infestations; interakce hostitele a parazita